Training students’ self-expression in English through portfolio assessment: A trial in English literature - Ha, Nguyen Thi Thu (VNU Journal of Foreign Studies, 2010)
Abstract. The recent approach to language teaching and learning has been focusing on communication as getting things done in the utilitarian sense. However, the core of communication, if it wishes to mean anything significant to the world at all, should be self-expression. The ultimate aim of foreign language teaching, therefore, should be to create individual learners who have their own foreign language personalities and know how to express themselves in the target language. Making use of primarily qualitative methods, this study is an investigation into the implementation of the literature portfolio and its effects on students’ self-expression in written and spoken English. With a carefully developed portfolio design and assessing criteria, the portfolio implementation not only uncovered the students’ problems but also brought about highly favorable learning processes and results regarding self-expression ability. In this study, the literature portfolio was used not only as a fair process assessment tool but also as a way to train students’ self-expression in English. Keywords:Self-expression, portfolio assessment, literature, qualitative research.